An Inquiry into the Domain of Information Science, with an Emphasis on Contributing Disciplines 1973 to 1998: Preliminary Results - Holmes, Boyd P. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
Most information scientists appear to agree that the discipline absorbs, within its boundaries, all or part of certain other subject areas. Certain scholars, including Borko, Garrison, Rayward, James G. Williams and Martha E. Williams, have published, separately, what each of them considers those disciplines to be. My research, for which I present preliminary results in this paper, will. . .